Free Radical-Scavenging Capacities, Phenolics and Capsaicinoids in Wild Piquin Chili (Capsicum annuum var. Glabriusculum) - Moreno Ramírez, Yolanda; Martínez Ávila, Guillermo Cristian Guadalupe; González Hernández, Víctor; Castro López, Cecilia; Torres Castillo, Jorge Ariel (2018)
Abstract: The total phenolic compounds content, free radical-scavenging capacity and capsaicinoid content in populations of wild Piquin chili (C. annuum) were studied. Aqueous and hydroalcoholic extracts from nine ecotypes were evaluated. High contents of phenolic compounds and free radical-scavenging capacities were observed for both extracts; however, the values that were found for the hydroalcoholic phase were substantially higher. LC-MS analysis allowed for the detection of 32 compounds, where apigenin-8-C-glucoside followed by vanillic acid 1-O-β-o-glucopyranosylester (IsomerIorII)and7-ethoxy-4 methylcoumarinwerethemostwidelydistributed;theywerefoundin more than 89% of the ecotypes. The diversity of identiﬁed phenolic compounds was different among ecotypes, allowing them to be distinguished by chemical diversity, free radical-scavenging capacities andheatScovilleunits.ThetotalcapsaicinoidcontentwashigherinPopulationI(23.5mg/gDW)than in Populations II and III, which had contents of 15.3 and 10.7 mg/g DW, respectively. This variability couldleadtophytochemicalexploitationandtheconservationofthenaturalpopulationsofwildchili.